Una traducción contemporánea del Canzoniere - Carrera Díaz, Manuel (Cuadernos de Filología Italiana, 2005)
This paper analyses the main characteristic features of Jacobo Cortines’ 1989 Spanish translation of Petrarch’s Canzoniere. It opens with a short history of all Spanish translations of this particular work, after which it focuses on the three most significant 20th-century ones, including Jacobo Cortines’. Since Canzoniere poses such great problems in metre, vocabulary and syntax, the achievements of the translator are carefully studied, the conclusion being that Cortines’ version excels all others, as it manages to combine a close rendering of the original text and a genuine artistic Spanish translation.